Pengaruh Hospitality Personel Pengamanan Penerbangan Terhadap Kepuasan Peumpang di Bandar Udara Sultan THaha Jambi - ZIkri, Muhazi Muhammad; Agoes Soebagio; Nunuk Praptiningsih (FTK UNSURYA, 2025)
This study examines the influence of aviation security personnel's hospitality on passenger satisfaction at Sultan Thaha Jambi Airport, motivated by the increasing number of passengers post-COVID-19 pandemic and observations of occasional unfriendliness and non-SOP compliant appearance of officers. The research aims to determine the impact of aviation security personnel's hospitality on passenger satisfaction and to identify aspects of hospitality that need improvement. Employing a quantitative approach with a questionnaire survey, primary data was collected from 97 passenger respondents at SCP 2 Sultan Thaha Jambi Airport through simple random sampling. Data was analyzed using SPSS, including validity, reliability, classical assumption tests, simple linear regression analysis, and hypothesis testing. The results indicate that aviation security personnel's hospitality has a positive and significant influence on passenger satisfaction, with a regression coefficient of 0.461 and a correlation coefficient of 0.398. However, aviation security personnel's hospitality only explains 15.8% of the variation in passenger satisfaction, while 84.2% is influenced by other factors. Tangible aspects, such as the physical appearance of officers and the condition of the inspection environment, were identified as areas most in need of improvement. In conclusion, aviation security personnel's hospitality plays a crucial role in passenger satisfaction, and improvements in tangible aspects are highly recommended to enhance the overall passenger experience.